PENDIDIKAN ISLAM PERSPEKTIF ZAKIAH DARADJAT - Nurlela, Siti; Azizah , Siti Nur; Rahayu, Siti; Sholihat, Siti; Rehani, Siti; Solihat, Siti (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Islamic education is an effort of physical and spiritual guidance at the level of individual and social life to develop human nature based on Islamic laws towards the formation of an ideal human being (insan kamil) who has a Muslim personality and commendable morals and is obedient to Islam so that he can achieve happiness in the world and the hereafter. The family is the first place where the education process takes place. Then continued with school and society. The difficulties in carrying out the task of educating are very pronounced, especially when faced with the reality that the influence of the environment is so strong, even surpassing the strength of other educational factors. At times like that, parents as the first educational force in the family environment must realize their role as educators completely towards their children. Departing from that background, the author then wants to discuss it in a thesis entitled "Islamic Education from the Perspective of Zakiah Daradjat". The purpose of this study is to determine the concept of Islamic education by Zakiah Daradjat which includes: the definition of Islamic education, the responsibility of Islamic education, the educational environment, and the concept of Islamic education according to Zakiah Daradjat. This research is a Library Research, meaning pure literature (looking for books and relevant books) with the title of the thesis. And using the Content Analysis technique means analyzing the contents of books that are relevant to the title and sourced from the results of library data collection. With the Descriptive Critical Analysis method, it means describing human ideas. In this case, tracing the theme raised which is related to this research, namely the concept of Islamic Education. The collected research data was analyzed using a deductive and inductive approach. The concept of Zakiah Daradjat, especially about Islamic education, shows that in the first stage of education there are dimensions in humans, namely; physical, intellectual, faith, morals, spiritual, beauty, social-community dimensions. And related to the responsibility of education in Islam which is held by parents, teachers and society, where all of that later their children will become the successors of their family, religion and country.